Islamic Education and Sharia Economy in Developing Pesantren Business Entities: A Case Study of BUMPes Nurul Jadid - Afif, Ahmad (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to explore the relationship between Islamic education and the sharia economy in the development of the Nurul Jadid Islamic Boarding School Business Entity (BUMPes) in Paiton, Probolinggo. Despite numerous studies on the pesantren's economic role, we still lack a comprehensive understanding of how Islamic education directly impacts the management and sustainability of BUMPes. This research uses a qualitative method with a case study approach, involving in-depth interviews with BUMPes managers, involved students, and teachers at the pesantren. We also obtained data by directly observing the business activities conducted by BUMPes. The research findings indicate that Islamic education provides a strong foundation for BUMPes managers in applying sharia economic principles, such as justice and transparency in transactions. Additionally, the students involved in BUMPes experience an increase in managerial skills and understanding of sharia financial management. This research also identifies the challenges faced in the implementation of Sharia economic principles, including the lack of resources and external support. Thus, this research emphasizes the importance of integrating Islamic education and sharia economics to support business development in the pesantren environment. We expect the results of this research to aid in the development of the educational curriculum in pesantren and offer valuable insights for policymakers to support sharia-based micro-enterprises.